THE EFFECTIVENESS OF ONLIMO UTILIZATION FOR WATER QUALITY MONITORING OF POLLUTION IN THE DOWNSTREAM AREA OF JANGKOK RIVER, MATARAM CITY - Aryanti, Janu Andina; Utama, Pramudya Bagas; Nabila, Maitsa Fikri (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The Jangkok River in Mataram City, Nusa Tenggara Barat, experiences severe pollution due to domestic and industrial waste. To monitor water quality in real-time, the Online Monitoring (ONLIMO) system has been implemented. This study aims to evaluate the effectiveness of ONLIMO compared to laboratory analysis in terms of accuracy, time, and cost. Physical and chemical parameters such as BOD, COD, DO, Nitrite, Nitrate, pH, TDS, and turbidity were analyzed using the Pollution Index (IP) method based on the Decree of the Minister of Environment No. 115 of 2003. The results showed an average Ci/Lij value of 1.70 with a maximum IP of 115.97 from ONLIMO, while the laboratory analysis produced an IP of 98.26 with a maximum Ci/Lij of 138.9. Nitrite (11.15–14.35) and turbidity (6.55–9.74) were identified as dominant contributors to pollution. In terms of efficiency, ONLIMO proved faster, with real-time monitoring and lower operational costs compared to laboratory methods, which require sample collection and manual analysis. However, ONLIMO has limitations in detecting certain parameters such as BOD. Overall, ONLIMO is considered efficient and effective for monitoring the water quality of Jangkok River, with potential improvements through the integration of additional methods for more accurate and comprehensive results.